2014
DOI: 10.1186/1471-2474-15-189
|View full text |Cite
|
Sign up to set email alerts
|

Improved lag screw positioning in the treatment of proximal femur fractures using a novel computer assisted surgery method: a cadaveric study

Abstract: BackgroundThe importance of the tip-apex distance (TAD) to predict the cut-out risk of fixed angle hip implants has been widely discussed in the scientific literature. Intra-operative determination of TAD is difficult and can be hampered by image quality, body habitus, and image projection. The purpose of this paper is to evaluate, through a cadaveric study, a novel computer assisted surgery system (ADAPT), which is intended for intraoperative optimisation of lag screw positioning during antegrade femoral nail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Screw positions were evaluated with the lag screw and proximal bone fragment (head and neck) and the safest seemed to be inferior middle and inferior posterior positions. A navigation system improved the lag screw position according to Regling et al ( 19 ) cadaveric study in operations carried out by less experienced and experienced surgeons and the median TAD was 12 mm and 13 mm, respectively. In another study, Hrubina et al ( 9 ) reported 297 patients with 308 hips treated with a dynamic hip screw; the complication rate was reported as 10% and the re-operation rate as 3.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Screw positions were evaluated with the lag screw and proximal bone fragment (head and neck) and the safest seemed to be inferior middle and inferior posterior positions. A navigation system improved the lag screw position according to Regling et al ( 19 ) cadaveric study in operations carried out by less experienced and experienced surgeons and the median TAD was 12 mm and 13 mm, respectively. In another study, Hrubina et al ( 9 ) reported 297 patients with 308 hips treated with a dynamic hip screw; the complication rate was reported as 10% and the re-operation rate as 3.9%.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] However, ADAPT is not yet widely adopted, and there exist only a few reports about ADAPT. [8,9] We reported the accuracy analysis of ADAPT in this study.…”
Section: Introductionmentioning
confidence: 93%
“…However, intraoperative determination of TAD is difficult and can be hampered by Fig. 1 The guide pin-shaft angle and anteversion before (a,∠α1; c, ∠β1) and after (b, ∠α2; d, ∠β2) the adjustment of the guide pin measured for one included patient the image quality, body habitus and image projection [14,15]. The repetitive adjustment of the main intramedullary nail and guide pin under the C-arm machine or a wide range of stripping and exposure may further increase the operative and fluoroscopy time and cause more complications and instability, especially for the surgeons who are lack of experience [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The TAD should be less than 25 or 27 mm in order to reduce the complications of the cut-out and nail breakage, fracture non-union and poor functional outcomes [ 9 13 ]. However, intraoperative determination of TAD is difficult and can be hampered by the image quality, body habitus and image projection [ 14 , 15 ]. The repetitive adjustment of the main intramedullary nail and guide pin under the C-arm machine or a wide range of stripping and exposure may further increase the operative and fluoroscopy time and cause more complications and instability, especially for the surgeons who are lack of experience [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%